Proteç\~ao das pessoas idosas dependentes: Análise comparativa da experiência internacional - Analia Soria Batista; Luciana Jaccoud; Luseni Aquino; Patrícia Dario El- Moor (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– Improvement in life expectancy and population ageing are worldwide phenomena that distinguish the demographic dynamics of nowadays societies. Therefore functional dependency and the quality of life of the frail elderly have grown into major issues in public agenda. This text aims to present and compare general aspects of the international experience in the field of long term care to frail elderly people. From the analysis of seven different cases (Germany, Spain, United States, France, Japan, United Kingdom and Sweden), we aim to identify both the specific approaches to functional dependency and the most relevant characteristics of the policies designed for this group. Aiming to contribute to the incipient discussion of the matter in Brazil, we also summarize the most important elements in the international debate on personal, domestic and medical long term care for frail elderly people.
Keywords: I38; J14; 330